Multiresolution Neural Networks for Imaging - Paz, Hallison; Novello, Tiago; Silva, Vinicius; Schardong, Guilherme; Schirmer, Luiz; Chagas, Fabio; Lopes, Helio; Velho, Luiz (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2022: Anais da XXXV Conference on Graphics, Patterns and Images, 2022)
We present MR-Net, a general architecture for multiresolution neural networks, and a framework for imaging applications based on this architecture. Our coordinate-based networks are continuous both in space and in scale as they are composed of multiple stages that progressively add finer details. Besides that, they are a compact and efficient representation. We show examples of multiresolution image representation and applications to texture magnification, minification, and antialiasing.